Disputas fronteiriças entre a Croácia e Bósnia e Herzegovina - João Vitor Marconato (Confins, 2021)
However, due to the region's tumultuous history, several conflicts have emerged between these newly independent nations. One of those clashes was the Bosnian war that ran between 1992 and 1995. After the end of that war in the Balkans, some small border disputes remain unsolved between Bosnia and Herzegovina and Croatia, which despite not causing major disagreements between countries, have an important symbolic value.